A seat by the hearth - Clipston, Amy (Clipston, Amy. Amish homestead novel., 2018)
"In the third installment of Amy Clipston's Amish Heirloom series, Priscilla Allgyer returns to the Amish community she'd dreamt of escaping and learns the hard lessons of love and forgiveness from a surprising source"--